Business Location Planning Assistance: Preservation of Traditional Culture of Kampoeng Batara Banyuwangi - Riza Bahtiar Sulistyan; Ratna Wijayanti Daniar Paramita (Institut Teknologi dan Bisnis Widya Gama Lumajang, 2021)
The era of the Covid-19 pandemic reduced many forms of business of the Indonesian people and as a result the economy also declined. During the pandemic, many people have been exposed to the products produced by the Banyuwangi people. This area is better known for its culture, one of which is the traditional children's playground culture which is preserved in Kampoeng Batara. In supporting the preservation of this culture, various bamboo handicraft businesses have been developed. The problem that occurs is that the production results quickly mushroom when stored for a long time. A Focus Group Discussion (FGD) has been conducted with the originators of Kampoeng Batara. The result is planning to make a storage place for bamboo handicraft production with proper air circulation and at the same time planning a heating machine to reduce the moisture content contained in the bamboo. In addition, it is also planned to build a toga garden so that children who play and the community feel comfortable in Kampoeng Batara. Part of the bamboo handicraft production will be donated in preserving the traditional culture of children's traditional playgrounds.